Colección “Mujeres lojanas en las artes”. Reconstrucción de la vida y obra de la pianista y pedagoga María Mercedes Bustamante Guaricela (1927-2016) - Ordóñez Salcedo, Scarlett Lizeth (2024)
The aim of this work is to make visible the life and work of the pianist and pedagogue Mercedes Bustamante and to preserve her legacy through the knowledge and interpretation of her compositions. This is achieved through the biographical reconstruction, compilation and edition of her compositions for children, presented in a musical booklet. The methods and techniques used for this purpose were divided into three phases. In the first phase, for the biographical reconstruction, the deductive and comparative-historical methods were used, as well as interviews and bibliographic research. In the second phase, which consisted of the transcription of the pianist works, the analytical-synthetic method was used, selecting six songs of different rhythms, to which the lyrics and the corresponding cipher were added. The last phase, aimed at disseminating and interpreting the children's works, was carried out using the synthetic method, compiling the children's works in the musical booklet "Discovering Mercedes Bustamante and her songs", which was then presented in a conference concert. The importance of this type of research makes it possible to review the data on the life and compositional work of the teacher, to preserve the musical works that have been forgotten, and to highlight her career as an artist and outstanding woman from Loja whose contribution to musical art is significant. Keywords: Women, music, biographical reconstruction, school works, music booklet.